“Religious Education” or “Teaching about Religion”? A Review of Compulsory Religious Culture and Ethics Lessons in Turkish Primary and Secondary Schools - Gündüz, Turgay (Religion and human rights, 2018)
Religious Culture and Ethics (RCE), a compulsory course in Turkish primary and secondary schools, is a highly debated issue with respect to education on religion. Discussions focus on whether the class is “religious education” with a confessional approach or “religious culture and ethics teaching” that adopts a non-confessional view. Following a short history of religious education courses in Turkish primary and secondary education, this study analyses the curriculum and the content of the RCE course from the perspective of two Islamic sects (madhhab) and religious education approaches to discuss the principal educational approach applied in the country. The study also analyses the argument that holds that RCE is a non-confessional lesson in terms of both content and application; and that, accordingly, there is no problem with its presence among compulsory courses in primary education. It is rather concluded that, since its inclusion within the primary and secondary education curricula as a compulsory lesson, RCE has never been non-confessional in terms of including other religions and beliefs as well as other sects within Islam. An examination of the sectarian sources of information on worship provided in these courses reveals that the current textbooks are explicitly grounded in the Hanafi School with regard to issues of Muslim obligations.